85 Phase 3 LITESPARK-033 (NCT07227402) Study of Belzutifan Plus Zanzalintinib Versus Cabozantinib for Recurrent Clear Cell Renal Cell Carcinoma During or After Adjuvant Anti–PD-(L)1 Therapy - Toni K Choueiri; Thomas Powles; Martin H Voss; Marc-Oliver Grimm; Kelly N Fitzgerald; Brian Simmons; Jerry Cornell; Joseph E Burgents; Priyanka Chablani; Cristina Suarez (The Oncologist, 2026)
Abstract Background Adjuvant pembrolizumab is the standard of care for patients with renal cell carcinoma (RCC) at increased risk for recurrence after nephrectomy. However, treatment options are needed following adjuvant anti–PD-(L)1 therapy because none of the currently available treatments for advanced RCC were evaluated in this setting. Belzutifan, a potent and selective hypoxia-inducible factor 2α inhibitor, is approved for advanced RCC following a PD-(L)1 inhibitor and vascular endothelial growth factor tyrosine kinase inhibitor (VEGF-TKI). Zanzalintinib is a multitargeted kinase inhibitor of VEGF receptors, MET, and the TAM family of kinases (TYRO3, AXL, and MER). VEGF-TKIs, such as cabozantinib, are approved as first-line treatment for advanced RCC and in patients who have received subsequent lines of therapy. Phase 2 studies combining a VEGF-TKI with belzutifan have shown promising antitumor activity in advanced clear cell RCC. The randomized, multicenter, open-label phase 3 LITESPARK-033 study (NCT07227402) is designed to evaluate the efficacy and safety of belzutifan plus zanzalintinib versus cabozantinib in participants with advanced clear cell RCC who experienced recurrence during or after anti–PD-(L)1 adjuvant therapy. Methods Eligible participants are aged ≥18 years with histologically confirmed, unresectable, advanced (stage IV) RCC with a clear cell component; have measurable disease per RECIST v1.1 as assessed by investigator; received adjuvant anti–PD-(L)1 therapy after nephrectomy; and experienced recurrence during or up to 24 months from the last dose of adjuvant therapy. Approximately 904 participants will be randomly assigned 1:1 to receive belzutifan 120 mg orally once daily plus zanzalintinib 60 mg orally once daily or cabozantinib 60 mg orally once daily. Treatment will continue until unacceptable toxicity or disease progression. Randomization will be stratified according to time of recurrence after adjuvant anti–PD-(L)1 therapy (≤6 months vs > 6 months after the last dose), International Metastatic RCC Database Consortium risk (favorable vs intermediate vs poor), and presence of sarcomatoid features (yes vs no). Primary end points are progression-free survival per RECIST v1.1 as assessed by blinded independent central review (BICR) and overall survival. Secondary end points are objective response rate and duration of response per RECIST v1.1 as assessed by BICR, and safety. The study is open and currently enrolling as of November 26, 2025. Results Combining targeted agents with different mechanisms of action has been a successful strategy in treating RCC. The therapeutic approach of combining the TKI zanzalintinib with the HIF-2α antagonist belzutifan may enhance therapeutic benefit. Conclusions N/A